1994
DOI: 10.1002/path.1711740308
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the c‐met proto‐oncogene product in normal skin and tumours of melanocytic origin

Abstract: The proto-oncogene c-met product (c-MET) is a receptor tyrosine kinase and functions as a receptor for hepatocyte growth factor (HGF). Although the function of c-MET has yet to be fully clarified, HGF stimulates the phosphorylation of tyrosyl residues on c-MET and triggers the signal transduction pathways, resulting in a contribution to the malignant progression of melanonocytes with synergic factors such as basic fibroblast growth factor and mast cell growth factor. Using immunohistochemical methods, we have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 13 publications
0
35
1
Order By: Relevance
“…Surprisingly, we observed that Met was also localized in the nucleus of several tumors. While this phenomenon has been observed in melanocytic and lung tumors, 54,55 to our knowledge, this is the first report of a nuclear localization of Met in ovarian cells. Unexpected nuclear localization in cancer tissues has also been reported for other growth factor receptors, such as those of the ErbB family, and was associated with the proliferative status of the cells.…”
Section: Discussionmentioning
confidence: 48%
“…Surprisingly, we observed that Met was also localized in the nucleus of several tumors. While this phenomenon has been observed in melanocytic and lung tumors, 54,55 to our knowledge, this is the first report of a nuclear localization of Met in ovarian cells. Unexpected nuclear localization in cancer tissues has also been reported for other growth factor receptors, such as those of the ErbB family, and was associated with the proliferative status of the cells.…”
Section: Discussionmentioning
confidence: 48%
“…Other RTKs showing strong expression include Erb-B2, IGF1R, and Met. Robust c-met, but not HGF/SF, expression has been observed in melanoma tissue and cells, and in some cases has been associated with progression to the metastatic state (Natali et al 1993;Saitoh et al 1994;Rusciano et al 1995;Hendrix et al 1998). In human interconverted uveal melanoma cells, which are highly aggressive and preferentially disseminate to the liver, c-met expression has been correlated to high motogenic response and invasiveness (Hendrix et al 1998).…”
Section: Rtks and Malignant Melanomamentioning
confidence: 99%
“…Interaction with receptors for these ligands, the proto-oncogenes c-Met and c-Kit, respectively, results in regulation of melanocyte proliferation and/or differentiation, mediated through signal transduction and protein phosphorylation [4]. Previous reports [7,16] showed that the effects of HGF and SCF occasionally differ between benign and malignant melanocytes. For example, Halaban et al [7] have shown that HGF could act as a potent mitogen for melanocytes, whereas cell proliferation is independent of the presence of exogenously supplied HGF when melanocytes become malignant.…”
Section: Introductionmentioning
confidence: 98%